Small towns of North Ossetia in the system of socio-economic development of the North Ossetian ASSR - Svetlava A. Khubulova; Zalina V. Sosranova; Eda V. Khubulova (Кавказология, 2022)
The article studies the problems of the emergence and further development of small towns on the territory of the North Ossetian ASSR. For the first time, the sources introduced allow us to trace the dynamics of the process of the emergence of small towns on the territory of the North Ossetian ASSR. It was found that the separation from the total mass of rural settlements as a transfer to the position of urban settlements did not happen by chance. In several settlements by this time, there were several large, economically designed enterprises that could become city-forming. These include factories for processing non-ferrous metal ores in Alagir, an oil refinery in Mozdok, canneries in Ardon, etc. It was found that some settlements specialized in processing agricultural products, while others became quite large industrial zones in the republic.In the pre-war years (1938), the small town of Alagir appeared. This is because the reequipment of military equipment required a large amount of non-ferrous metal ores, manganese, etc. For their modern extraction and processing, new enterprises were created, which became the core of new settlements-cities.Other small towns appeared on the map with the ASSR in 1950 and 1964. Thus, the city of Beslan was a major railway interchange through which the movement of goods, passenger traffic, etc. was carried out. In addition, a maize mill successfully operated in Beslan, which ranked second in Europe in terms of capacity. The cities of Ardon and Digora played a much smaller economic role, which in the 1960s and 1970s found themselves in a transitional situation. In these small settlements, the influence of the traditional rural way of life was still strong. However, the process of transition to the state of urban life was gaining momentum.